EVALUATION OF THE INFLUENCE OF MULTIPLICATIVE INTERFERENCE ON THE BIT ERROR PROBABILITY OF COHERENT RECEPTION OF SIGNALS WITH MULTIPOSITION PHASE SHIFT KEYING - TUROVSKY, OLEKSANDR; MELESHKO, TETIANA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
In the article, there is a new topical scientific task to estimate the impact of the multiplicative problem on the probability of the bit pardon of the coherent signal reception with the rich positional phase shift keying. The model for evaluating the injection of a multiplicative input on the immovability of a bit pardon of a coherent signal reception with rich positional phase manipulation has been disassembled and submitted. The given model is based on the movable characteristics of the appearance of a symbolic and bit pardon to a signal with a rich positional phase modulation of the received level of the intensity of the multiplicative input for different values of the signal-to-noise ratio at the input of the coherent receiver.The results of the evaluation of the immovability of the bit pardon of the coherent receiving signal with a rich positional phase manipulation with the presence of the multiplicative input signal in the warehouse showed the advance. A multiplicative task with an apparent mean value of intensity μ = 0.1, an amplitude dispersion of 0.01 and a phase dispersion of 0.01 rad2 for BPSK and QPSK is given with a bit-cutting intensity of 0.001 signal/noise ratio 0.3 to 1 dB. For signals with 8PSK and 16PSK, the attenuation can be 2.5 and 5 dB, obviously. With increased dispersion fluctuations, the negative effect of the multiplicative wave increases significantly. In the district channel, for the reliability of receiving signals with a small position (M < 8), there is a larger influx of fluctuations in amplitude, lower phase. At M>8, the inflow of phase fluctuations on the value of the smoothness of the pardon is essentially growing. The presented results can be applied in the development of new and improved existing telecommunication systems based on signal transmission technology with multi-position phase shift keying. The solution of the problem of estimating the influence of multiplicative interference on the probability of a bit error of coherent reception of input signals is aimed at improving the efficiency of functioning of telecommunication facilities based on a signal with multiposition phase shift keying.
Keywords: multi-position phase shift keying; interference immunity of the telecommunication network; multiplicative interference